Pengembagan Sistem Penjualan Kios Sarto Sapi Berbasis Website - Erix Yoga Pratama Putra Bakti; Maria Atik Sunarti Ekowati (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
The development of a Website-Based Sarto Sapi Kiosk Sales System in writing this thesis is carried out to improve efficiency and service quality in the process of selling Sarto Sapi kiosk products, and to explain the importance of adopting website technology in the sales business to increase accessibility and convenience for customers. The goal of this development is to create a sales system that is responsive, intuitive and integrated with the inventory system. The development method used includes analysis of user needs, responsive user interface design, and integration with an accurate inventory system. The result of this development is a website-based Sarto Sapi kiosk sales system that is equipped with product search features, shopping carts, and a secure online payment system. This system also allows kiosk owners to manage and update products, as well as track sales and financial reports. The output of this development is increased operational efficiency and growth of the Sarto Sapi kiosk business through the adoption of modern website technology..